(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
Cloud computing environments face significant challenges in managing real-time workloads due to dynamic resource demands, heterogeneous infrastructure, and the need for cost-efficient operations. Traditional static or rule-based orchestration techniques often fall short in adapting to fluctuating workloads, leading to suboptimal resource utilization and increased latency. This paper explores the application of Artificial Intelligence (AI) to cloud orchestration, focusing on real-time workload management to optimize performance, scalability, and cost-effectiveness. We propose an AI-driven orchestration framework leveraging machine learning and reinforcement learning algorithms to predict workload patterns, automate resource provisioning, and dynamically allocate tasks across multi-cloud and hybrid cloud infrastructures. The framework integrates real-time monitoring and feedback loops to continuously refine decisionmaking processes, ensuring responsiveness to workload variations. We evaluate the proposed model using real-world cloud workload traces and benchmark datasets from 2023–2024, comparing its performance against traditional heuristics and rule-based orchestration systems. Results indicate significant improvements in workload balancing, reduced response time by 25%, and up to 30% cost savings in resource utilization. The system also demonstrates robust scalability across heterogeneous cloud environments. The paper discusses implementation challenges, including model training overhead, data privacy concerns, and integration with existing cloud management platforms. Finally, future research directions focus on enhancing explainability of AI decisions, incorporating edge-cloud orchestration, and leveraging federated learning for decentralized intelligence. Our findings highlight the transformative potential of AI-driven cloud orchestration to meet the evolving demands of real-time workload management in complex cloud ecosystems.